(3QSGdI aj GdhMes - (3GdNLfOj , eMeO Hf YHO GddWja Hf eMeO GdegdHj GdGROj GdCUagGfj, UOQ GdOjf CHj HcQ,J (B552 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdJeS (B+(3efj HYV GdeNdUjf Cf CMd YbO cdGe GdTjN GdQFjS QMeg Gddg, aj aSGO GdTghI, aHGOQJ Edj eG GdJeS eSJYjkf HGddg JYGdi s
(3BNQgG (B:s
(3gPG eG SfM di ai gPG GdehVhY , hGddg hdi GdJhajb , hefg GdgOGjI Edi GdJMbjb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B142s
(3GfXQgG eY HSJGf GdCWHGA Qbe (B349 - 351s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B217 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B192s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B113 s
Keywords: (3GdWHs